The three-phase contact line shape and eccentricity effect of anisotropic wetting on hydrophobic surfaces - Kashaninejad, Navid (2013)
This paper experimentally evaluates the combined effects of eccentricity, relative spacing, and viewing directions on the wetting conditions and the three-phase contact line shapes of hydrophobic surfaces patterned with discrete micropillars. Different techniques to depict the tortuosity of the contact line between the water droplet and microstructured surfaces are presented. First, square micropillars with different values of normalized eccentricity, ε*, and relative spacing, D*, were fabricated using a double casting replication technique. Subsequently, the contact angles were measured along different viewing angles by gradually rotating the sample from 0° to 180°. The contact angle distribution was found as a periodic function of the viewing angle whose period depends on the micropillar eccentricity. The results showed that anisotropy increases by increasing the micropillar eccentricity or decreasing the pillar relative spacing. However, the effect of changing the micropillar eccentricity was much more pronounced. Micropillars with ε* = 0.75 and smaller D* showed maximum degrees of anisotropic wetting and droplet distortion corresponding to 7% and 15%, respectively. Using the measured droplet aspect ratio, corrugated shapes of the three-phase contact line of the micropillars were also reconstructed. Finally, a simple yet effective semi-analytical model, based on Fourier series curve-fitting of the experimental data, was developed to describe the equilibrium 3D shape of the droplet on anisotropic surfaces. Experimental and simulation results reveal that the degrees of anisotropic wetting and droplet distortion were directly proportional to the energy barriers of the system, resulting from the noncircular corrugated shape of the three-phase contact line. The obtained results may further shed light on the underlying mechanism influencing anisotropic wetting on micropatterned surfaces.